Implementing the World Mental Health Survey Initiative in Portugal - rationale, design and fieldwork procedures - Xavier, Miguel (2019)
Xavier, M., Baptista, H., Mendes, J. M., Magalhães, P., & Caldas-de-Almeida, J. M. (2013). Implementing the World Mental Health Survey Initiative in Portugal - rationale, design and fieldwork procedures. International Journal of Mental Health Systems, 7(1), [19]. https://doi.org/10.1186/1752-4458-7-19